A model of successful DNP and PhD collaboration. Issue 2 (February 2019) - Cowan, Linda; Hartjes, Tonja; Munro, Shannon
ABSTRACT: Background and purpose: Within nursing education, the existence of two graduate-level programs has created some challenges. Role confusion between the practice-focused Doctor of Nursing Practice (DNP) and the research-focused Doctor of Philosophy (PhD) is compounded by competition for similar positions. Collaboration between DNP and PhD nurses, however, benefits the health care system and patients. Methods: The complementary skills of these two groups of nurses are detailed, and a model for building PhD-DNP partnerships is presented based on a collaborative PhD-DNP project that resolved a negative trend in outcomes from cardiac surgery. The clinical pathway created by the project met national benchmarks, improved interprofessional staff communication, and resulted in uniform and improved patient care. Conclusions: Although role differentiation for doctoral nurses can be challenging, role integration is critical. Building collaborative partnerships between these groups of nurses benefits the health care system, as well as patients, and this partnership is sustainable through successful collaborative projects. Implications for practice: Doctoral-prepared nurses must understand each other's background and education and focus on what each can contribute. In the beginning, as with any collaborative relationship, collaborators must discuss and agree on ground rules, team roles, responsibilities, and time line for projects.